Does celebrity endorsements have an impact or influence the purchase intention or buying behaviour of the youth in India - Khanna, Sneha (2012)
The use of celebrity endorsement is becoming more and more popular these days and is used by marketers and companies in order to generate more sales, create or increase brand recognition and also to increase brand awareness. The main purpose of this research is to find out whether celebrity endorsements influence the purchase behavior or intentions of the Indian consumers. This research is aimed to get a better understanding of which factors of a celebrity influences the Indian consumers, attitudes of a consumer when a celebrity suffers a negative publicity, brand management and consumers’ purchasing behavior or intentions towards celebrity endorsed products. India has a huge market for the endorsers and celebrities from various streams endorse products. Cricketers and Bollywood stars are the most popular ones chosen to endorse products ranging from pens to washing detergents, mobile networks to cars, every segment uses celebrities to have their products and brands endorsed. This research focuses on the impacts of the cricketers and Bollywood stars that are not just popular in India, but globally known and popular as celebrities too. Based on the purpose and research questions, an interview questionnaire was prepared to understand the purchase behavior and determine what factors do the Indian consumers actually look at or qualities they look for when they purchase any product or brand in the market. The interviews were held in person with the candidates who were willing to participate in this research and the interviews were held through the means of online communications, telephone calls. Data was gathered and collected from these responses and are used further to discuss and analyzed to draw conclusions.